Report on coal deposits in the Codroy River Valley [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's Nfld. : Robinson, 1917)
Running title: Geological Survey of Newfoundland report for 1897. "For the year 1897." Electronic reproduction. Mode of access: Internet. 44